Transport of Water and Solutes across Maize Roots Modified by Puncturing the Endodermis (Further Evidence for the Composite Transport Model of the Root). - Steudle, E. (1993)
The effects of puncturing the endodermis of young maize roots (Zea mays L.) on their transport properties were measured using the root pressure probe. Small holes with a diameter of 18 to 60 [mu]m were created 70 to 90 mm from the tips of the roots by pushing fine glass tubes radially into them. Such wounds injured about 10-2 to 10-3% of the total surface area of the endodermis, which, in these hydroponically grown roots, had developed a Casparian band but no suberin lamellae. The small injury to the endodermis caused the original root pressure, which varied from 0.08 to 0.19 MPa, to decrease rapidly (half-time = 10-100 s) and substantially to a new steady-state value between 0.02 and 0.07 MPa. The radial hydraulic conductivity (Lpr) of control (uninjured) roots determined using hydrostatic pressure gradients as driving forces was larger by a factor of 10 than that determined using osmotic gradients (averages: Lpr [hydrostatic] = 2.7 x 10-7 m s-1 MPa-1; Lpr [osmotic] = 2.2 x 10-8 m s-1 MPa-1; osmotic solute: NaCl). Puncturing the endodermis did not result in measurable increases in hydraulic conductivities measured by either method. Thus, the endodermis was not rate-limiting root Lpr: apparently the hydraulic resistance of roots was more evenly distributed over the entire root tissue. However, puncturing the endodermis did substantially change the reflection ([sigma]sr) and permeability (Psr) coefficients of roots for NaCl, indicating that the endodermis represented a considerable barrier to the flow of nutrient ions. Values of [sigma]sr decreased from 0.64 to 0.41 (average) and Psr increased by a factor of 2.6, i.e. from 3.8 x 10-9 to 10.1 x 10.-9 m s-1(average). The roots recovered from puncturing after a time and regained root pressure. Measurable increases in root pressure became apparent as soon as 0.5 to 1 h after puncturing, and original or higher root pressures were attained 1.5 to 20 h after injury. However, after recovery roots often did not maintain a stable root pressure, and no further osmotic experiments could be performed with them. The Casparian band of the endodermis is discontinuous at the root tip, where the endodermis has not yet matured, and at sites of developing lateral roots. Measurements of the cross-sectional area of the apoplasmic bypass at the root tip yielded an area of 0.031% of the total surface area of the endodermis. An additional 0.049% was associated with lateral root primordia. These areas are larger than the artificial bypasses created by wounding in this study and may provide pathways for a "natural bypass flow" of water and solutes across the intact root. If there were such a pathway, either in these areas or across the Casparian band itself, roots would have to be treated as a system composed of two parallel pathways (a cell-to-cell and an apoplasmic path). It is demonstrated that this "composite transport model of the root" allows integration of several transport properties of roots that are otherwise difficult to understand, namely (a) the differences between osmotic and hydrostatic water flow, (b) the dependence of root hydraulic resistance on the driving force or water flow across the root, and (c) low reflection coefficients of roots.